Portuguese geographical discoveries of West Africa and the Gold Coast during the modern era - lasselat, elguerri (The Algerian Historical Journal, 2026)
The Gold Coast region or Ghana is one of the areas that the Europeans have been grappling with since its discovery by the Portuguese to the British occupation, and has followed the rule of its coasts dutch, Germans, Danes and Swedes, and this journey of detection shows us the value of gold as a reason for the European cost to Africa and the detection and subsequent occupation of Africa, contrary to what colonial propaganda promoted from the spread of civilization and the recovery of African peoples from ignorance and poverty, as reasons for the occupation of Africa, Portugal had a pioneering role in uncovering most of the coastal West Africa, but the internal conditions that deprived it of most of its property with its weak military and settlement presence in the coastal stations were discovered, thus declining their role in Africa since the 16th century AD.